The association between antimicrobial resistance and HIV infection: a systematic review and meta-analysis. (June 2021) - Olaru, Ioana D.; Tacconelli, Evelina; Yeung, Shunmay; Ferrand, Rashida A.; Stabler, Richard A.; Hopkins, Heidi; Aiken, Alexander M.; Kranzer, Katharina
Abstract: Objectives: People living with HIV (PLWH) are at increased risk of infections with resistant organisms due to more frequent healthcare utilization. Our objective was to investigate the association between HIV and antimicrobial resistance (AMR). Methods: We searched MEDLINE, EMBASE, Web of Science, LILACS and African Journals Online. Studies were eligible if they reported on AMR for colonization or infection with bacterial pathogens (excluding mycobacteria and bacteria causing sexually transmitted infections) and were stratified by HIV status, species and antimicrobials tested. Pooled odds ratios were used to evaluate the association between HIV and resistance. Results: In total, 92 studies published between 1995 and 2020 were identified. The studies included the following organisms: Staphylococcus aureus ( n = 47), Streptococcus pneumoniae ( n = 28), Escherichia coli ( n = 6) and other Gram-negative bacteria. PLWH had a 2.12 (95%CI 1.36–3.30) higher odds for colonization and 1.90 (95%CI 1.45–2.48) higher odds for infection with methicillin-resistant S . aureus, a 2.28 (95%CI 1.75–2.97) higher odds of infection with S. pneumoniae with decreased penicillin susceptibility, and a 1.59 (95%CI 0.83-3.05) higher odds of resistance to third-generation cephalosporins in E. coli and Klebsiella pneumoniae . Conclusion: This review shows an increased risk of AMR in PLWH across a range of bacterial pathogens and multiple drug classes. The lack of laboratory capacity for identifying AMR, and limited access to alternative treatment options in countries with the highest burden of HIV, highlight the need for more research on AMR in PLWH. Overall, the quality of studies was moderate or low, which may impact the findings of this review.